Current state of groundwater exploitation in the Rioverde valley, San Luis Potosí, Mexico. - Francisco Aguilar Ortega (Tecnología y ciencias del agua, 2010)
The Rioverde valley can be geographically divided in two areas: North, with calcium sulfate water, C4S1 and C5S1 water classes, and undrinkable water, used for crop production, and South, with calcium bicarbonate, C1S1, C2S2 and C3S1 water classes, and drinking water for different possible uses. Due to the excellent water quality in the south, the effects of greater use are expected to be more intense in this area. Considering the above, the objective was to recognize and prioritize the factors influencing the utilization of groundwater for agricultural use and its implications in the depletion of the phreatic level in the south portion of the Rioverde valley. The working procedure was: to collect and analyze census data and files on the use of groundwater at the Rioverde valley, and to do a survey among farmers who own wells. The topics were hydraulic infrastructure, organization, crop systems, production, profitability and agricultural marketing, credit, and government support. Census information and archive data were synthesized in tables. Information from the survey was analyzed using multivariate analysis (principal components and TWISPAN). The results indicate that the use of groundwater can be characterized with the application of water and crop pattern variables. Also, farmers can be grouped based on the acceptance of water meters governing the extraction, on the adoption of technologies for the extraction and application of water, and on crops patterns.